Stereotype movement recognition in children with ASD - Rodrigues, José L. (2012)
The Autism Spectrum Disorders (ASD) covers different events, being one of them body rocking, mouthing, and complex hand and finger movements [1]. The traditional methods for recording the number of occurrences and duration of stereotypes are inadequate and time consuming. Therefore, it was used a commercial system with accelerometers sensors that records the movement of wrist and sends the collected data through a wireless network to the computer. Statistical methods were used to characterize the signal acquired from a previously expressed stereotypy. The parameters that were analyzed are: RMS, Standard Variation, Peaks and Valleys. At the end, the proposed methodology facilitates to identify behavioral patterns special relevant when studying interaction skills in children with ASD.